Assessment of genes controlling Area Under Disease Progress Curve (AUDPC) for stripe rust (P. striiformis f. sp. Tritici) in two wheat (Triticum aestivum L.) crosses - Irfaq, M.; Mir Ajab; Ma Hongxiang; Gss Khattak (Цитология и генетика, 2009)
Genetic effects on controlling stripe rust resistance were determined in two wheat crosses, Bakhtawar-92 x Frontana (cross 1) and Inqilab-91 x Fakhre Sarhad (cross 2) using Area under Disease Progress Curve (AUDPC) as a measure of stripe rust resistance. Генетические эффекты контроля устойчивости к желтой ржавчине злаков были определены в двух скрещиваниях пшеницы Bakhtawar-92 x Frontana (скрещивание 1) и Inquilab-91 x Fakhre-Sarhad (скрещивание 2) с использованием Area Under Disease Progress Curve (AUDPC) для измерения устойчивости. Генетичні ефекти контролю стійкості до жовтої іржі злаків були визначені в двох схрещуваннях пшениці Bakhtawar-92 x Frontana (схрещування 1) и Inquilab-91 x Fakhre-Sarhad (схрещування 2) з використанням Area Under Disease Progress Curve (AUDPC) для вимірювання стійкості.